Death due to choking caused by swallowing Sushi Rolls - Satoshi Furukawa Katsuji Nishi; Satomu Morita; Masahito Hitosugi; Hiroshi Matsumoto (Forensic Science Today - Peertechz Publications, 2017)
Setsubun is associated with The Chinese New Year, or Lunar Calender which was used for centuries in Japan, so this is a coming of spring festival as well as the traditional new year. It is still an important event in Japan.  Setsubun properly refers to the day before the coming of any of the four seasons. So, this is actually spring Setsubun. Setsubun dinner is simple, sushi rolls. The proper way to eat this dinner is to face a certain direction, and eat the entire sushi roll without stopping. We experienced an autopsy case of a death due to swallowing down sushi rolls. The deceased was a 54-year-old man who was found dead in the restroom. An autopsy revealed congestive changes of organs. We report here an autopsy case.